Rethinking historiographical disparities and pathways to reconciliation in the Georgian-Abkhazian conflict - Shalva Kikalishvili; David Bragvadze (Frontiers in Political Science)
This paper critically examines the historiographical disparities that have shaped Georgian and Abkhazian perspectives on their shared and often contested past, a division further exacerbated by Soviet-era influences and modern nationalist narratives. The primary aim is to illuminate how these divergent interpretations of history contribute to enduring misunderstandings and conflict, highlighting the need for a historiographical re-evaluation as a step toward reconciliation. Additionally, this study explores the tension between militaristic and peace-oriented approaches to conflict resolution, with a firm advocacy for peace-building measures. By presenting a comprehensive analysis of historical narratives and projecting a vision for a shared future, this discourse aims to foster a constructive dialogue that transcends historical grievances and promotes cooperative action. Ultimately, the paper aspires to contribute to a holistic understanding of the Georgian-Abkhazian conflict and to outline pathways toward a sustainable and mutually beneficial coexistence.